Alpha-Pinene-encapsulated lipid nanoparticles diminished inflammatory responses in THP-1 cells and imiquimod-induced psoriasis-like skin injury and splenomegaly in mice - Li, Tao-Yu; Liang, Wan-Li; Zhao, Yi-Ming; Chen, Wan-Dong; Zhu, Hong-Xia; Duan, Yuan-Yuan; Zou, Han-Bo; Huang, Sha-Sha; Li, Xiao-Jun; Zhang, Wei Kevin (Frontiers in Immunology, 2024)
Psoriasis, a persistent skin condition caused by the disorder of the immune system, impacts approximately 1.25 million individuals globally. Nevertheless, the presence of adverse effects in conventional clinical drugs necessitates further exploration of novel medications or combination therapies to mitigate these reactions and enhance their effectiveness. Hence, our intention here in this paper is to utilize the lipid nanoparticle delivery system for overcoming the volatility and hydrophobic properties of α-pinene, a naturally occurring compound renowned for its antiinflammatory and antiviral effects, and further explore its potential pharmacological applications both in vitro and in vivo. The production of α-pinene lipid nanoparticles (APLNs) was achieved through the utilization of high pressure homogenization methods. APLNs was successfully fabricated with enhanced stability and water solubility. Meanwhile, the application of APLNs could drastically reduce the expression of lipopolysaccharide (LPS)-induced inflammation-related factors in THP-1 cells. Administration of APLNs to a mouse model of auricular swelling could effectively reduce redness and swelling in the auricles of mice as well. Furthermore, APLNs were also found to alleviate skin damage in mice with Imiquimod (IMQ)-induced psoriasis model, as well as decrease the levels of psoriasis-related protein nuclear factor kappa-B (NF-κB) and interleukin-17 (IL-17), interleukin-23 (IL-23), and other inflammation-related cytokines. More importantly, utilization of APLNs successfully mitigated the systemic inflammatory reactions in mice, resulting in the reduction of spleen-to-body ratio (wt%) and of inflammatory cytokines' expression in the serum. Overall, our results suggest that with the help of lipid nanoparticle encapsulation, APLNs possess a better pharmacological effect in anti-inflammation and could potentially serve as an anti-psoriasis drug.